2020
DOI: 10.1177/1078155220967722
|View full text |Cite
|
Sign up to set email alerts
|

Antiemetic medication efficacy during EPOCH and R-EPOCH treatment

Abstract: Introduction This study aims to determine the adequacy of current institutional standard practice for CINV prophylaxis for EPOCH and R-EPOCH at The Ohio State University James Cancer Hospital. Methods Single-center, retrospective analysis was performed including all patients receiving EPOCH or R-EPOCH chemotherapy for Non-Hodgkin’s lymphomas from 1/1/2012 to 6/30/2017. The primary endpoint was rate of CINV events, which included usage of more than 50 percent of available doses of breakthrough antiemetics while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…It is critical to report our rates of CINV from those reporting emetogenicity of highly emetogenic multiday chemotherapy for hematologic malignancies. In one study with a similar population of 111 patients with lymphoma receiving DA-EPOCH or DA-R-EPOCH, 48.6% of patients receiving prophylactic antiemetics without NK1RA experienced a CINV event during their treatment [4] compared to 58.3% of our non-NK1RA patients who did not achieve CR. Another study examining patients with acute leukemia receiving induction with moderately emetogenic multiday chemotherapy, reported that the patients who received 5HT3RA-only prophylaxis experienced a 32.6% CR [15], similar to our without NK1RA group's CR of 41.7%.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…It is critical to report our rates of CINV from those reporting emetogenicity of highly emetogenic multiday chemotherapy for hematologic malignancies. In one study with a similar population of 111 patients with lymphoma receiving DA-EPOCH or DA-R-EPOCH, 48.6% of patients receiving prophylactic antiemetics without NK1RA experienced a CINV event during their treatment [4] compared to 58.3% of our non-NK1RA patients who did not achieve CR. Another study examining patients with acute leukemia receiving induction with moderately emetogenic multiday chemotherapy, reported that the patients who received 5HT3RA-only prophylaxis experienced a 32.6% CR [15], similar to our without NK1RA group's CR of 41.7%.…”
Section: Discussionmentioning
confidence: 77%
“…A subgroup analysis revealed that men in the NK1RA group had improved CR, while women had similar CR in both the NK1RA and without NK1RA groups. Overall, these data add to the growing body of evidence describing the unmet clinical need for adults with hematologic malignancies receiving multiday chemotherapy and experiencing CINV [3,4,[14][15][16].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations